2017
DOI: 10.1038/s41598-017-01674-8
|View full text |Cite|
|
Sign up to set email alerts
|

A genome-wide association study of anorexia nervosa suggests a risk locus implicated in dysregulated leptin signaling

Abstract: We conducted a genome-wide association study (GWAS) of anorexia nervosa (AN) using a stringently defined phenotype. Analysis of phenotypic variability led to the identification of a specific genetic risk factor that approached genome-wide significance (rs929626 in EBF1 (Early B-Cell Factor 1); P = 2.04 × 10−7; OR = 0.7; 95% confidence interval (CI) = 0.61–0.8) with independent replication (P = 0.04), suggesting a variant-mediated dysregulation of leptin signaling may play a role in AN. Multiple SNPs in LD with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…Research on candidate genes examined the serotonergic system (5-HT system), dopaminergic system, and opioidergic system that affect appetite, reward mechanism, mood, and weight; nevertheless, statistically significant results have not been presented so far [51]. Genome wide studies showed a relation between chromosomes 1, 11, and 12 and genes related to leptin regulation, lipid and glucose metabolism, serotonin receptor activities, and the immune system [52][53][54][55]. This genetic presentation is also consistent with the clinical presentation of anorexia.…”
Section: Genetic Explanationsmentioning
confidence: 99%
“…Research on candidate genes examined the serotonergic system (5-HT system), dopaminergic system, and opioidergic system that affect appetite, reward mechanism, mood, and weight; nevertheless, statistically significant results have not been presented so far [51]. Genome wide studies showed a relation between chromosomes 1, 11, and 12 and genes related to leptin regulation, lipid and glucose metabolism, serotonin receptor activities, and the immune system [52][53][54][55]. This genetic presentation is also consistent with the clinical presentation of anorexia.…”
Section: Genetic Explanationsmentioning
confidence: 99%
“…The inactivation of EBF1 in mice leads to a decrease in circulating leptin levels, in line with the observations of very low leptin levels made in human AN patients. In addition, another SNP (rs4704963) in EBF1 showed genome-wide significant interaction with psychosocial stress on obesity traits [83]. In a sample of 3,495 AN cases and 10,982 controls, rs4622308 near the v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 3 (ERBB3) gene was significantly associated with AN [84].…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…Only 2 studies to date have identified SNPs significantly associated with AN [83,84]. To gain the statistical power necessary for further genome-wide significant results, research efforts should focus on the recruitment of large case-control cohorts.…”
Section: Limitations Of Genetic and Epigenetic Approachesmentioning
confidence: 99%
“…After adjustment for BMI four loci in/near LEP, SLC32A1, GCKR, and CCNL1 remained robustly associated with leptin levels (Kilpeläinen et al, ). One study found suggestive evidence for a variant‐mediated (rs929626 in EBF1 : Early B‐Cell Factor 1 gene) disordered leptin signalling in patients with anorexia nervosa (AN; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…. One study found suggestive evidence for a variant-mediated (rs929626 in EBF1: Early B-Cell Factor 1 gene) disordered leptin signalling in patients with anorexia nervosa (AN; Li et al, 2017).…”
mentioning
confidence: 99%